Speaking Out: Introductory - Ikey, Olivia (Études Inuit Studies, 2020)
Conference retranscription « Living in Northern Quebec: Issues and Challenges of Appropriate and Meaningful Living Environments for Inuit Communities”, Special session “LINQ’s Day-Long Special Session”, Inuit Studies Conference 2019. October 3, 2019, Université du Québec à Montréal. Retransciption de la conférence « Habiter le Nord québécois: Enjeux et défis d’aménagements appropriés et significatifs pour les communautés Inuit », Session spéciale HLNQ, Congrès d’Études Inuit 2019. 3 octobre 2019, Université du Québec à Montréal.